A study of Automobile industry in India - Mr Jai Prakash; Dr. S. S. Jadhav (Innovative Research Thoughts, 2022)
In recent years, the automotive industry has gained a sizable percentage of the global market. Automobile manufacturers are attempting to corner the market by using a wide variety of business tactics, including an increased emphasis on tiny automobiles and fuel-efficient cars with low market prices. A number of environmental problems, including carbon emissions, warmer temperatures, and so on, have surfaced in response to the auto industry's increased market dominance. Automobile manufacturers in such a context are under double pressure: one to protect the environment, and another to sustain the company's long-term financial viability. The firm's success may be evaluated by looking at its finances, operations, and marketing strategies. This article attempts to establish a connection between the company's performance and sustainable growth via the adoption of green initiatives, and it also proposes a method for the adoption of the green initiatives at the business. This study would explore the many green strategies that businesses are doing, including green marketing, green supply chain management, green innovation, etc. The research would look at the realities and potentials of green initiatives for the growth and survival of the company and the planet. This report draws on exploratory research and a thorough review of the relevant literature to provide its results.